Using the social rate of discount in evaluating public investments in the Philippines (PIDS Policy Notes, 2014)
What discount rate to use in evaluating public investments has been a subject of long and intense debate. Varying views come from both theory and practice. The common practice is to use a range of estimates and perform a sensitivity analysis. But behind the numbers and proposed methodologies are unresolved questions and, to some degree, unsettled debate on what should be the social rate of discount. This Policy Note puts forward some suggestions on the "appropriate" social rate of discount for use in benefit-cost analysis of public investments in the Philippines.